Towards 2030: Sustainable Development Goal 8: Decent Work and Economic Growth. A Sociological Perspective - Andrzej Klimczuk; Minela Kerla; Magdalena Klimczuk-Kochańska; Piotr Toczyski; Delali A. Dovie (Frontiers Media, 2024)
This volume addresses the eighth Sustainable Development Goal. It not only enquires into its global promulgation and into individual local, national, and international cooperative programs in support of it, but it also considers the framing and elaboration of the goal, its adaptation to particular geographical contexts, stakeholder involvement in it, and the issues concerning decent work conditions worldwide.
Keywords: E24; J60; 330; SDG8; unemployment